The association between obesity and eating behaviour among primary school children in Kota Kinabalu - Lily Shuzeen Kimin (2023)
Childhood obesity has become one of our country's major concerns, and has been rising dramatically over the years. The latest statistic from National Health and Morbidity Survey (NHMS) shows that the national prevalence of obesity in 2015 was 11.9% and has escalated to 14.8% in 2019 (NHMS, 2019). According to Roy et al., 2011, specific eating behaviours that have been associated with obesity include under-responsiveness to internal satiety cues and over-responsiveness to external food cues such as taste, smell, availability and emotions. Yet there is inadequate number of study present in Sabah to describe children eating behaviours despite of the increasing disease burden. This study aims in determining the prevalence of childhood obesity in Sabah as well as look into the association in eating behaviours between children nutritional status in Kota Kinabalu. A cross-sectional study involving 484 students (aged 6-12 years old) was conducted in five primary schools at Kota Kinabalu, Sabah. The schools were selected based on multistage stratified sampling method and convenience sampling method. Primary school children with a known medical condition such as bronchial asthma, type-1 diabetes mellitus or those with a prolonged use of oral steroids was excluded from the study. Sociodemographic details and anthropometric measures both parents and children, and eating behaviours of children were assessed using Children eating behaviour questionnaire (CEBQ). Age-adjusted body mass index (BMI) z-scores were calculated according to the WHO recommendations to assess nutritional status. Out of 484 respondents, there were 198 (40.9%) male participants and 286 (59.1%) female participants. The prevalence of childhood obesity among primary school children is 13.2%. The mean scores of ‘Food Approach’ subscales (FR, EF, EOE, DD) showed higher mean score in overweight and obese groups as compared to mean score in normal weight group. The mean scores of ‘Food Avoidance’ subscales (SE, EUE, FF) showed lower mean score in overweight and obese groups as compared to mean score in normal weight group. This study has proved that “Food approach” subscales were positively associated to excess weight in children.